1976
DOI: 10.1212/wnl.26.5.447
|View full text |Cite
|
Sign up to set email alerts
|

Migraine attacks

Abstract: Twenty-six patients with migraine attacks were treated for 3 to 16 months with flufenamic acid (125 mg four to six times per attack), an inhibitor of prostaglandin synthesis and action. In 25 patients the drug afforded symptomatic relief in 195 of 200 treated attacks. Side effects observed were mild dyspepsia (eight patients) and severe upper gastrointestinal symptoms (two patients). None of the eight patients treated with placebo reported any relief (20 attacks). The "common" antimigraine drugs afforded sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1977
1977
2000
2000

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…A clinical trial with fenamates was successful in primary dysmenorrhea in which PGF2" plays an important role [Schwartz et al} 1974]. In a previous study [Vardi et al, 1976] we found that fenamates were effective in alle viating migrainous attacks.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…A clinical trial with fenamates was successful in primary dysmenorrhea in which PGF2" plays an important role [Schwartz et al} 1974]. In a previous study [Vardi et al, 1976] we found that fenamates were effective in alle viating migrainous attacks.…”
Section: Discussionmentioning
confidence: 83%
“…However, it should be mentioned that in another series published by us [Vardi et al, 1976] 2 patients abandoned treatment because of severe nausea and vomits.…”
Section: Treatment and Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…This is followed within 20-30 min by intra-and extracranial vasodi latation, related initially to a serotonin-in duced release from lung tissue of circulating prostaglandins, and later to low circulating levels of serotonin itself. Raskin [1982] is not convinced of the importance of prostaglan dins in the pathogenesis of this disorder, pointing to conflicting evidence in the litera ture [Vardi et al, 1976;Lindegaard et al" 1980] on the effect of prostaglandin-antago nist drugs in the abortion of migrainous at tacks. Nor is he impressed by the hypothesis of an exclusive vascular mechanism.…”
Section: Episodic Pain Disordersmentioning
confidence: 99%
“…10 Estrogen withdrawal, which is presumably associated with falling prolactin levels, may precipitate migraine. 16,17 If prostaglandin F 2a is associated with a complicated migrainous attack, one should expect elevated prolactin plasma levels during a migrainous attack. 13 On the other hand the potent prolactin stimulating drug metoclopramide, seems to be effective in the treatment of migraine, which would rule out any simple association between high prolactin plasma levels and migraine.…”
Section: Introductionmentioning
confidence: 99%